METHYL MERCURY IN GREEN MUSCLE (Mytilus viridis L.) FROM FISH MARKET MUARA ANGKE : BEFORE AND AFTER COOKING - Ermin K. Winarno; Winarti Andayani; Agustin Sumartono (Indonesian Journal of Chemistry, 2009)
The determination of methyl mercury content in green muscle (Mytilus viridis L.) that were taken from Pasar Pelelangan Ikan Muara Angke, Jakarta Bay has been carried out. Sampling was taken in November 2005 and March 2006, the samples were bought from the green muscle sellers. The aim of this research is to know the effect of cooking on the content of methyl mercury in green muscle. Samples were homogenized, weighed and washed with aceton and toluene. After washing, the homogenized material was added with HCl solution, extracted with toluene, then the methyl mercury content in toluene extract was analyzed using gas chromatography. The results of this research showed that methyl mercury concentration in raw and cooked green muscle respectively were 0.803 + 0.019 mg/g and 0.443 + 0.035 mg/g (in November 2005) and 0.096 + 0.014 mg/g and 0.079 + 0.016 mg/g (in March 2006) respectively. The methyl mercury content in raw (in November 2005) was higher than in cooked green muscle as permitted concentration in the sea biota by WHO and FAO, it is 0.5 ppm (mg/g), on the other hand the result of the second sampling in March 2006 showed that methyl mercury content in green muscle was lower than permitted concentration. Cooking process of the green muscle decreased methyl mercury content 44.85% (sampling in November 2005) and 17.71% (sampling in March 2006), because methyl mercury that bonded to protein were distributed to boiling water. Methyl mercury content in green muscle after cooking was still lower than the permitted concentration.